TRANSFER PENGETAHUAN PADA PERUSAHAAN KELUARGA (Studi pada Perusahaan Keluarga Arya Mas) - Prasetio, Yuda; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2018)
Transfering the knowledge to a family enterprise is crucial to the survival of a family enterprise. This study aims to see the process of knowledge transfer that occurs in the family company that is seen from the dimension of leadership value transfer and leadership knowledge transfer.In this study, the method that is used here is a qualitative method which uses an interview approach, documentation, and case studies for collecting the data. This reaserch was conducted in arya mas family company that is located in salatiga city.The result of this study indicate that the transfer of knowledge that occurs in arya masfamili company does not occur perfectly, the transfer of knowledge that occurs in the family company only in the aspects of competence, capability, technical, and operational